Effect of antisecretory treatment on gastrointestinal microbiota - D. Ye. Rumyantseva; A. S. Trukhmanov; A. V. Kudryavtseva; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present the data on the effect of proton pump inhibitors to gastrointestinal microbiota. Summary. Proton pump inhibitors (PPI) - is a basic class of drugs for acid-related diseases treatment. The data proving gastrointestinal microbiota alteration at PPI administration were obtained. Possible mechanism may include the direct action on bacterial H+/ K+-ATPase, as well as indirect action on the environment pH. Increase of Lachnospiraceae family bacteria quantity in esophagus after PPI treatment and unclassified Clostridial families alone with reduction of Methylobacteriaceae family were observed. Decrease of Moraxellaceae, Flavobacteriaceae, Comamonadaceae, Methylobacteriaceae family bacteria and increase of Erysipelotrichaceae family and unclassified Clostridiales order families was noted in the stomach. Long-term PPI intake can result in development of small-intestinal bacterial overgrowth syndrome, and also can be associated to development of Clostridium difficile-associated disease. Conclusion. The data of few available studies demonstrate microbiota changes throughout gastrointestinal tract at PPI intake. However these results are inconsistent and provide no definite answer whether this changes are beneficial or harmful that requires further studies.